Effectiveness of Alkaline Pretreatment and Acetic Acid Hydrolysis on the Characteristics of Collagen from Fish Skin of Snakehead - Wulandari Wulandari; Pipih Suptijah (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2015)
Fish skin is one of marine byproducts potential for alternative source of collagen. This studyinvestigated the effectiveness of alkaline and acetic acid pretreatment on the characteristics ofcollagen from skin snakehead fish. The concentrations of alkaline pretreatment were 0.05; 0.1; 0.15and 0.2 M for 2, 4, 6, 8, 10 and 12 hours, acetic acid concentrations were 0.05 M, 0.1 M, 0.15 M and0.2 M for 1 and 2 hours. The experimental design used for alkaline and acetic acid pretreatmentwas factorial completely randomized design. The result showed that the concentration of alkaline0.05 M for 6 hours have significant effect on the elimination of non-collagen protein (p<0.05),whereas for the optimum acetic acid at a concentration 0.1 M for 2 hours significantly differenton solubility and swelling. Extraction yields of collagen was 16%, with characteristics of whiteness66.67%, protein content 96.21%, viscosity 10 cP, Tmax 159.9oC and glass transition temperature78.55oC. The dominant amino acid composition were glycine (27.11%), proline (13.87%) andalanine (12.58%). Functional groups collagen from skin snakehead fish has β-sheet structurewhich is a characteristic of collagen.